Risk factors in deceased donor liver transplantation: a single centre experience - S. I. Zubenko; A. R. Monakhov; M. A. Boldyrev; V. R. Salimov; A. D. Smolianinova; S. V. Gautier (Вестник трансплантологии и искусственных органов)
Deceased brain-dead donor liver transplantation (LT) is a high-risk intervention. The outcome depends on a large number of modifiable and non-modifiable factors. Objective: to analyze our own experience and identify preoperative and perioperative prognostic factors for poor outcomes in LT. Materials and methods. The study included 301 liver transplants performed between January 2016 and December 2021. Donor and recipient characteristics, intraoperative data, perioperative characteristics including laboratory test data, and the nature and frequency of complications were used for the analysis. Results. The 1-, 3- and 5-year recipient survival rates were 91.8%, 85.1%, and 77.9%, respectively; graft survival rates were 90.4%, 83.7%, and 76.7%, respectively. The most significant predictors of poor outcome of LT on the recipient side were biliary stents (HR 7.203, p < 0.01), acutely decompensated cirrhosis (HR 2.52, p = 0.02); in the postoperative period, non-surgical infectious complications (HR 4.592, p < 0.01) and number of reoperations (HR 4.063, p < 0.01). Donor creatinine level (HR 1.004, p = 0.01, one factor analysis; HR 1.004, p = 0.016, multivariate analysis) was the only reliable prognostic negative factor. Conclusion. LT taking into account established risk factors will improve surgery outcomes and help personalize the therapy for each patient.